Response to Anwar Tlili‘s paper ―Efficiency and social inclusion: implications for the museum profession (Cadernos de Sociomuseologia, 2012)
I have been asked to respond to Anwar Tlili‘s paper, and I propose to do this in four steps. I will follow Anwar‘s line of arguments closely. I will be dealing in turn withStep no. 1: Profession and ProfessionalizationStep no. 2: Social InclusionStep no. 3: ManagerialismStep no. 4: Museum Education and Training